Characteristics of Students' Metacognitive Ability in Solving Problems using Awareness, Regulation and Evaluation Components - Anita Adinda; Heri Purnomo; Desi Rahmatina; Nur Choiro Siregar (Universitas Syiah Kuala, 2023)
The process of solving absolute value problems is not only associated with the simplification of equations or inequalities. Students also need to pay close attention, ask the right questions, carry out the right strategies, and acquire adequate information. This step is essential to prevent students with good metacognitive ability from drawing wrong conclusions. The research discusses the metacognitive characteristics of mathematics education students in solving absolute value problems from the awareness, regulation and evaluation components. Participants consisted of 101 students from four state universities in the city of Malang. Data were obtained through written answers, transcripts of think aloud, and interviews. The data collected were analyzed to determine their metacognitive abilities in terms of awareness, regulation and evaluation components. The result showed that the metacognitive ability of low-skilled students only exists in the awareness component, which is thinking about what is being asked. Furthermore, those medium capable of the awareness component still lack adequate thinking ability. In the regulation and evaluation components, students do not realize that there are still inappropriate steps in solving problems and fail to check the correctness of their answers. However, high-ability students can solve problems in different ways and easily distinguish accurate information using effective strategies. Learn how the metacognitive characteristics of students in solving non-routine absolute value application questions, provides space for educators to be able to create appropriate learning models.